2021
DOI: 10.3390/ijerph18031073
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Electromagnetic Field Exposure from 5G Mobile Communications at 28 GHZ in Adults and Children Users for Real-World Exposure Scenarios

Abstract: The recent development of millimeter-wave (mmW) technologies, such as the fifth-generation (5G) network, comes with concerns related to user exposure. A quite large number of dosimetry studies above 6 GHz have been conducted, with the main purpose being to establish the correlation between different dosimetric parameters and the skin surface temperature elevation. However, the dosimetric studies from 28 GHz user equipment using different voxel models have not been comprehensively discussed yet. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Entering into more detail on the numerical results for each investigated configuration, the user absorbed power density peaks obtained for the homogenous skin model were in line with the work of Morelli et al [24], where the exposure levels caused by a microstrip patch antenna array (at 28 GHz) for mobile applications were evaluated in different human models with a single skin layer. The peak values of the different human models were indeed in the range between 0.13-0.43 W/m 2 for an input power of 15 dBm (32 mW).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Entering into more detail on the numerical results for each investigated configuration, the user absorbed power density peaks obtained for the homogenous skin model were in line with the work of Morelli et al [24], where the exposure levels caused by a microstrip patch antenna array (at 28 GHz) for mobile applications were evaluated in different human models with a single skin layer. The peak values of the different human models were indeed in the range between 0.13-0.43 W/m 2 for an input power of 15 dBm (32 mW).…”
Section: Discussionsupporting
confidence: 77%
“…Efforts have also been made to determine the maximum averaging area for power density that limits the maximum temperature increase to a given threshold for frequencies above 6 GHz for plane wave, dipoles and array antenna [21]. Furthermore, some research involved the use of realistic anatomical models to assess the exposure levels in terms of specific absorption rate and absorbed power density [22][23][24], whereas others focused on multilayer modeling of the skin when exposed to plane-wave to underline how, at high frequencies, a detailed skin model is necessary to correctly estimate the assessment of exposure levels [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The rampant and permanent increase in both public and occupational exposure to various EMF fuels ongoing discussion on health concerns, with the recent implementation of 5G as the most prominent example [ 51 , 52 ]. The complexity of such physical stimuli, in particular, necessitates considering the applied conditions such as frequency and field strength, as well as the fundamental medical condition of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…The results represented the SAR and radiation penetration in the brain model, and therefor SAR, decreases with increasing depth and frequency. In 16 the SAR values in head model of children and adults at 28 GHz (30 mW) and a microstrip antenna as a field source have been simulated. The results showed that absorption in tissues decreasing rapidly in depth.…”
Section: Introductionmentioning
confidence: 99%